Treatment outcomes of glandular urethral strictures: a systematic review and network meta-analysis - V. A. Vorobyov; E. Yu. Prokopyev; A. M. Pushkaryov; M. I. Kogan (Вестник урологии, 2025)
Introduction. Distal urethral strictures account for up to 18% of anterior urethral narrowing and are frequently linked to lichen sclerosus, iatrogenic trauma, or failed hypospadias repair, causing marked voiding dysfunction and reduced quality of life. The absence of unified guidelines for selecting the optimal management strategy necessitates a critical analysis of the accumulated data. This systematic review with network meta-analysis summarises the current evidence base regarding the efficacy and safety of surgical and endoscopic approaches for strictures of the glans urethra.Objective. To assess the efficacy and safety of various treatments for distal urethral strictures (glandular urethra, navicular fossa, and external urethral meatus) through a systematic review and meta-analysis, including a network meta-analysis.Materials & methods. A systematic literature search was conducted in PubMed, MEDLINE, Embase, and Cochrane Library following PRISMA guidelines. Studies reporting recurrence rates, patient satisfaction, complication rates, and long-term efficacy of different treatments, including meatotomy, one-stage and two-stage urethroplasty, and minimally invasive methods (dilation, urethrotomy), were included.Results. The analysis included 15 studies with a total of 422 patients. The average recurrence rate after minimally invasive treatment (dilation, urethrotomy) was 60 – 80%, while after reconstructive surgery (urethroplasty), it was 10 – 15% (OR 10; 95% CI 5 – 20). Patient satisfaction exceeded 90% after urethroplasty. The network meta-analysis showed that two-stage and one-stage BMG urethroplasty were the most effective methods, with a success probability > 90%. Minimally invasive techniques had significantly lower long-term effectiveness (SUCRA ≤ 30%).Conclusion. Surgical reconstruction is the preferred treatment method for glandular urethral strictures. Both two-stage and single-stage urethroplasty provide the best long-term outcomes, whereas meatotomy may be an option for limited strictures. Endoscopic treatment is associated with a high recurrence rate and should be reserved for select cases only.